Análise de aspectos de usabilidade em interações naturais via interfaces multimodais - Cossio, Lucio Polese (2015)
The presence of computing devices grows day by day, making them available at the most different scenarios of use. The system’ interaction needs to evolve together with the technology to provide a better user experience in these distinct environments. Several studies in the multimodal interfaces area advocate the benefits of these interfaces, because of the availability of more natural ways of interaction, allowing the users more efficiency and satisfaction for the execution of system tasks. In the last years, devices that allow more natural interactions, started to become widely available to the public and to be used more often, showing great potential of use. This work presents a research with the goal of understand and compare the preference and use acceptance of these technologies, through the implementation and analysis of a presentation system, using a Kinect device and an Android smartphone. The system allows users to execute slide and image presentations to an audience, using speech, body gestures or the smartphone (touch gestures) for interaction. The first work phase focused in the interaction definition through individual interviews and focus groups execution. After that, the system was implemented following the results of the previous phase. At the end, the evaluation of the system was done through the use and execution of tasks in a class environment (without audience). The obtained results show the diverse users’ perspective of use of the different systems interaction modes. The smartphone was the most precise and preferred technology by most of the users because is easy to use, although, some participants showed great interest in the use of the other modalities, showing a potential for acceptance of them. The intended system context of use have some challenges, since body gestures and speech are also used by system users to communicate with other people at the same time, considered by some of the participants as unsuitable for the situation. The system tests were executed in an isolated environment, and future tests should be applied in a real use context for more precise evaluation.